Cyclic diGMP regulates production of sortase substrates of Clostridium difficile and their surface exposure through ZmpI protease-mediated cleavage - Fairweather,NF; Peltier,J; Shaw,HA; Couchman,E; Dawson,LF; Choudhary,JS; LU,Y; Kaever,V; Wren,BW (Journal of Biological Chemistry, 2015)
Background: Bacteria use variousmechanisms to anchor their surface proteins,including a sortase enzyme.Results: Covalent anchoring of proteins to thepeptidoglycan in Clostridium difficile and itsregulation by cyclic-di-GMP and proteaseactivity are demonstrated.Conclusion: A novel regulatory mechanism ofcell wall protein anchoring is found.Significance: Elucidating how proteins areanchored may shed light on control of bacterialcolonization in vivo.